The cosmological doctors of classical Greece: first principles in early Greek medicine - Camden, David H. (Cambridge University Press, 2023)
Why did some doctors in Classical Greece feel compelled to study the universe as a whole? How could cosmological principles be employed in clinical practice? This book explores the works of the cosmological doctors, such as On Breaths, On Flesh, and On Regimen, and argues that they form part of a much broader reorganization of medical knowledge in the fifth and fourth centuries BCE. These healers used cosmological principles as a supplement to, rather than a replacement of, more traditional approaches to health and disease, creating theories about the cosmos whose obscurities can best be understood as the products of medical thinking. Through fresh readings of many ancient sources, the book revises customary views of the intersections between medicine and cosmology in Classical Greece and advances our understanding of one of the most remarkable periods in the history of ancient thought.